A qualitative study of health professionals' views on using iPads to facilitate distraction during paediatric burn dressing changes - Elizabeth Green; Julia Cadogan; Diana Harcourt (SAGE Publishing, 2018)
Introduction: Distraction is a non-pharmacologic pain management technique commonly used to avert a person's attention from procedural pain and distress during stressful procedures such as treatment after a burn injury. In recent years, computer tablets (such as iPads) have been used within paediatric burns services to facilitate distraction by way of apps, games, cartoons and videos during dressing changes. However, we know very little about health professionals' experiences of using them in this context. Methods: The current study explored health professionals' experiences of using iPads to facilitate distraction during paediatric burn dressing changes. Fifteen health professionals from a single paediatric burns unit were interviewed. Thematic analysis revealed two key themes: (1) the iPad is a universal panacea for distraction; and (2) trials and tribulations. Discussion: Participants considered iPads to be potentially useful and effective distraction tools, suitable for use with a wide range of patients with burn injuries including young children, adolescents and young adults. However, issues including health professionals' understandings of one another's roles, the challenge of working in a busy burns service, and lack of experience and confidence were identified as possible barriers to their use within routine burn care. Training for staff on the use of iPads as a means of facilitating distraction, development of guidelines and a review of how they are incorporated into routine burn care are recommended.